E-Learning: Justifications and Obstacles - Khoury, Ansar; Nasir Eddeen, Lubna; Saadah, Doaa; Harfoushi, Osama (International Journal of Emerging Technologies in Learning (iJET), 2011)
Many educational institutions have adopted E-Learning system or are thinking to adopt it in their educational systems. As a nearly recent system, many do not know the exact meaning of E-Learning, or why should it be used? After using it, will the institution face any problems? And what are the best solutions for these problems? This paper aims to answer all the above questions. In addition, it discusses the ways to transform traditional learning systems to E-Learning, and how to measure the advantages of this transformation. Finally, the students' views of E-Learning show that they prefer e-learning over traditional system.